Jewellery box / Effah Nadiah Muhamad Aliza - Muhamad Aliza, Effah Nadiah (2022)
The Islamic Complex Putrajaya (Malay: Kompleks Islam Putrajaya) is an administrative building complex for Malaysian government agencies. Putrajaya Islamic Complex is located in Precinct 3, Putrajaya and is motivated by modern Islamic architecture. This building has the concept of light, transparency and dynamics. Inspired by the parable of "nur" which is light as stated in Sura An-Nur verse 35.